2021
DOI: 10.1016/j.tifs.2021.02.040
|View full text |Cite
|
Sign up to set email alerts
|

Pea protein ingredients: A mainstream ingredient to (re)formulate innovative foods and beverages.

Abstract: Background: Pea (Pisum sativum) proteins are emerging as a popular alternative to those conventional (deriving from animal and soy) due to their high protein content with interesting functionality, sustainability, availability, affordability and hypo-allergenicity. This popularity has been parallel to an intensive research from protein isolation to their applications. Pea protein ingredients can be obtained through wet extraction, dry fractionation or more recently mild fractionation. As such, commercial pea p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
77
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(87 citation statements)
references
References 136 publications
1
77
0
Order By: Relevance
“…People have also consumed pulse crops for at least 10,000 years (Mudryj et al., 2014; references therein). Plant‐based proteins have gained popularity in recent years due to environmental, human health, and animal welfare concerns (Asgar et al., 2010; Boukid, 2021; Boukid et al., 2021; Choudhury et al., 2020; He et al., 2020; McCrory et al., 2010; Sabaté & Soret, 2014; Vatansever et al., 2020), with soybean and pea proteins currently leading the market (Bashi et al., 2019). The global meat alternatives, for example, had a value of US$4.1 billion in 2017 and projected to reach US$3.5 billion by 2026 (Vatansever et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…People have also consumed pulse crops for at least 10,000 years (Mudryj et al., 2014; references therein). Plant‐based proteins have gained popularity in recent years due to environmental, human health, and animal welfare concerns (Asgar et al., 2010; Boukid, 2021; Boukid et al., 2021; Choudhury et al., 2020; He et al., 2020; McCrory et al., 2010; Sabaté & Soret, 2014; Vatansever et al., 2020), with soybean and pea proteins currently leading the market (Bashi et al., 2019). The global meat alternatives, for example, had a value of US$4.1 billion in 2017 and projected to reach US$3.5 billion by 2026 (Vatansever et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Pea protein is favored for its high digestibility, lower allergenicity, and gluten‐free character (Lu et al., 2020; Shen et al., 2016; Zhao et al., 2020). Pea also has health benefits such as lowering serum cholesterol and blood pressure, balancing blood sugar, and reducing the risk of certain cancers (Boukid et al., 2021; and references therein). The economic value of pea protein was US$32 million in 2017 and is projected to hit US$176 million by 2025 (Sable, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the increased viscosity allowed water to be effectively retained, preventing syneresis. It has been reported that biochemical processes, such as those involving LAB fermentation, yeast, or enzymes, can impart more favorable emulsification, viscosity, or creaming properties when manufacturing products using PP, producing stable products that are not vulnerable to syneresis [26].…”
Section: Syneresismentioning
confidence: 99%
“…However, plant-based proteins have demonstrated to be good alternatives for their replacement in products with dietary restrictions (e.g., lactose-free) and in vegetarian and vegan foods. Moreover, plant-based proteins are more sustainable as they have a lower carbon footprint [11,12]. Examples include pea [13,14] and soy proteins [15], which have been reported for emulsions production.…”
Section: Introductionmentioning
confidence: 99%